Knowledge of Ancient Culture and Architectural Criticism in the 1960s: Arche in the Modern Architecture - Volchok, Yury P. (Actual Problems of Theory and History of Art, 2015)
Knowledge of ancient culture played an important role in the establishment of scientific grounds for Russian architectural criticism in the 1960s. Of all numerous layers of the general history of architecture, including temporal and methodological, it was the ancient culture that has stepped forward as it gives a prominent characteristic of its time in close connection with the peculiarities of a profound attention to the opportunities given by a systematic approach to acquisition of new scientific knowledge. It is usual in science criticism to discuss problems of shaping and style formation basing on historical material, i.e. on the information about the past. In the 1960s, due to increased attention to the peculiarities of establishment of the New in all its manifestations, the methods for knowledge of history aimed at the past also turned to the future. And the focus on the Recent Age has become the foundation for such knowledge. However, in our case the Recent Age is not the result of any creative work but revelation of the New in the course thereof. The problem of structure of the New understood as the Beginning = arche — came to the foreground. It has formed one more layer of architectural science focused on knowledge about the history of ancient culture as one of the components of theoretic design.
Keywords: architectural heritage; contemporary time; ancient time; arche; new; creative; constructivism; values; research methods